Vertical jump force-time metric differences between 3x3 and 5x5 professional male basketball players - Pulley, T.; Cabarkapa, D.; Cabarkapa, D.; Adanin, N.; Philipp, N.; Fry, A. (International Journal of Exercise Science Conference Proceedings, 2024)
The countermovement vertical jump (CVJ) is one of the most commonly used methods for neuromuscular performance assessment in the applied sports setting. However, despite a rapid increase in the popularity of 3x3 basketball, no research to date has examined the CVJ profile of these athletes and whether it is different than the 5x5 basketball players` profile.